PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP PRESTASI BELAJAR PADA MATERI KELILING DAN LUAS BANGUN DATAR DI KELAS IV SDN CEUNGCEUMJAYA - Arief Hidayat Afendi; Rizal Fuad Noor; Rahmat Permana; Meiliana Nurfitriani (PGSD Universitas Muhammadiyah Cirebon, 2022)
ABSTRACT The background of this research is the low learning achievement of students in mathematics subjects based on interview data. This study aims to improve the learning achievement of fourth grade students at SDN Ceungceumjaya by using a problem based learning (PBL) learning model. This type of research is a quantitative research method of pre-experimental designs in the form of one-group pretest-posttest design. The research subjects were class IV SDN Ceungceumjaya with a total of 28 students. The object of this research is learning achievement on the material of circumference and area of ??flat shapes using problem based learning (PBL) learning model. The instrument used in this study was a test. The data analysis technique used in this research is quantitative analysis and descriptive quantitative analysis.The results showed that the application of the PBL learning model could improve mathematics learning achievement in the material of circumference and area of ??flat shapes for class IV SDN Ceungceumjaya seen from the average pretest value for students who were not given treatment, which was 40.00 while for students who were given treatment or group. posttest that is 83.39. It can be seen that there is a significant difference between the results of student achievement before being given treatment and after being given treatment. Keywords: Learning Achievement and Learning Model Problem Based Learning (PBL) ABSTRAK Latar belakang penelitian ini adalah masih rendahnya prestasi belajar peserta didik pada mata pelajaran matematika berdasarkan data wawancara. Penelitian ini bertujuan untuk meningkatkan prestasi belajar peserta didik kelas IV SDN Ceungceumjaya dengan menggunakan model pembelajaran problem based learning (PBL). Jenis penelitian ini adalah kuantitatif metode penelitian pre-eksperimental designs bentuk one-group pretest-posttest design. Subjek penelitian adalah kelas IV SDN Ceungceumjaya yang berjumlah 28 peserta didik. Objek penelitian adalah prestasi belajar pada materi keliling dan luas bangun datar dengan menggunakan model pembelajaran problem based learning (PBL). Instrumen yang digunakan pada penelitian ini adalah tes. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis kuantitatif dan analisis kuantitatif deskriptif. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran PBL dapat meningkatkan prestasi belajar matematika materi keliling dan luas bangun datar kelas IV SDN Ceungceumjaya dilihat dari nilai rata-rata pretest pada peserta didik yang tidak diberikan perlakuan yaitu 40,00 sedangkan untuk peserta didik yang diberikan perlakuan atau group posttest yaitu 83,39. Terlihat perbedaan yang signifikan antara hasil prestasi peserta didik sebelum diberikan perlakuan dan sesudah diberikan perlakuan. Kata Kunci: Prestasi Belajar dan Model Pembelajaran Problem Based Learning (PBL)